mTOR Inhibitors in the complex treatment of high-risk vascular malformations in children - I.M. Benzar; D.V. Zhumik (Хірургія дитячого віку, 2020)
Recent experimental and clinical studies demonstrated that mTOR receptor inhibitors can stop the progression of vascular malformations and significantly improve patients’ quality of life. This is possible due to the interruption of the chain of phosphatidylinositol-3-kinase (PI3K) / AKT / mTOR reactions.